Efficacy of Indocyanine Green Fluorescence Angiography in Preventing Anastomotic Leakage After McKeown Minimally Invasive Esophagectomy - Luo, Rao-Jun; Zhu, Zi-Yi; He, Zheng-Fu; Xu, Yong; Wang, Yun-Zheng; Chen, Ping (Frontiers in Oncology, 2021)
Background Indocyanine green (ICG) fluorescence angiography (FA) was introduced to provide real-time intraoperative evaluation of the vascular perfusion of the gastric conduit during esophagectomy. However, its efficacy has not yet been proven. The aim of this study was to assess the usefulness of ICG-FA in the reduction of the rates of anastomotic leakage (AL) in McKeown minimally invasive esophagectomy (MIE). Methods From June 2017 to December 2019, patients aged between 18 and 80 years with esophageal carcinoma were enrolled in the study and each patient underwent McKeown MIE. Patients were divided into two groups, those with or without ICG-FA. The patient demographics and perioperative outcomes were comparable between the two groups. The primary outcome was the rate of AL. Results A total of 192 patients were included: 86 in the ICG-FA group and 106 in the non-ICG-FA group. Overall, 12 patients (6.3%) had AL; the rate of AL was 10.4% in the non-ICG-FA group, which was significantly higher than the 1.2% in the ICG-FA group. Conclusions ICG-FA has the potential to reduce the rate of AL in McKeown MIE.